FONOLOGI POSLEKSIKAL BAHASA MELAYU LOLOAN BALI - SUPARWA, I NYOMAN (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2007)
Abstract This study aims to describe the rule of post lexical phonology finding in Malay Loloan Bali language. The finding covers the rule and the process of phonology and also the motivation of that process. The analysis was done by focusing on the phonology and syntax connection and also the phonology generative approach, therefore the process and the rule of sound change and also the distingtive fitur can be described. Generally, the change of post lexical sound in Malay Loloan Bali language is in form of contraction besides the rule of phonology border word. The sound change in that contraction process generally found in form of the sound change of particel such as demonstrative, preposition, and discourse particel that usually found if it is used in sentences and the sound change in environment of close sound in frase, so it can be covered in phonology post lexical rule. The motivation of the post lexical sound changes is the contraction process occuring the sound deletion. That contraction process caused by the desire of native speaker to use the language more economic and practice, such as deletion ? in preposition ke (ke ulu ? kulu ?ke utara?) or deletion i in demonstrative ini (karang ini ? karang ni ?sekarang ini?. Meanwhile, the sound change in border word of frase caused by anticipation of articulator and articulation when it produces that sounds, for example glaide insertion of [y] in frase (kaki ayam ? [kaki yayam] ?kaki ayam?) that usually shown in phonetice realitation.